Merging a practice-orientated approach with an engineering-driven product development: a case study on home improvement. (1st January 2012) - Haines, Victoria; Mitchell, Val; Mallaband, Becky
CALEBRE, a four year research project, is developing technologies to improve the energy efficiency of solid-walled housing in the UK, particularly in the owner occupied market. The engineering partners within the project require very specific information from user-centred design (UCD) practitioners in order to develop innovative technologies. However the project recognises that it is the 'soft factors' that must be addressed in order to make these measures acceptable and appealing to householders. This requires a deeper understanding of users' motivations for improving their homes and the complex interplay of factors relating to aesthetics, lifestyle, life events, energy efficiency and finance. This paper presents how a practice-orientated UCD approach was taken to inform an engineering-driven product development process. It describes two data collection methods used within CALEBRE specifically to address these challenges and focuses on the specific home improvement practice of replacing windows.